Kajian Material Komposit Sandwich pada Floor Panel Pesawat Terbang - Muhammad Labib Adyavit; Larasati Irischa Ramadhani; Mardiyati Mardiyati; Steven Steven (Mesin, 2023)
Sandwich composites have been used as lightweight materials in aircraft manufacturing for a long time, from balsa wood sandwich in the 1930s to honeycomb and fiber-reinforced polymers sandwich. Its characteristics are considered as a 'perfect' material for aircraft, which has high strength with low density. Sandwich composites are the common materials for aircraft floor panels. The core is usually made of Nomex or aluminum honeycomb, while the skin is made of 1 "“ 2 ply of carbon/glass fiber in epoxy resin composite. The core is usually constructed using the corrugating or expansion method, whilst the skins are usually constructed using the prepreg lay-up method. Both materials are combined together by a simple adhesive bonding. Being the most strictly regulated transportation method on the planet, floor panel manufacturers must abide by aircraft manufacturing companies and local aviation authority standards and specifications to ensure the product's safety. The purpose of this study is to determine the most used materials for aircraft floor panels and why is it widely used, to understand the manufacturing process, and to know the specifications and standards that need to be fulfilled.